The Relationship Between Selected Attraction Factors And Employees’ Retention : A Study In One Of The Hotel In Taiping Perak, Malaysia. - Yu, Wan Che (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study aims to determine the relationship between selected attraction factors (job security, pay, promotion opportunities, work environment) and employees’ retention in one of the hotel in Taiping Perak, Malaysia. Past researches focused on different elements of human resource practices, organizational practices, and other industries in or outside of Malaysia. The theory and model used in this study are the Maslow’s Hierarchy Theory and the Tower Perrin Total Reward Model. A quantitative method was used in this research which involved a set of closeended questionnaire and distributed to the employees who work in the selected hotel. This study was conducted in one selected hotel which located in Taiping Perak, Malaysia. The relationship between the selected attraction factors and employees’ retention in the selected hotel were analysed by using the Pearson Correlation Analysis while the dominant factor that influence the employees’ retention in the selected hotel was identified by using Multiple Regression Analysis. The results shown that there is a significant relationship between the selected attraction factors and the employees’ retention. Besides, there is also a high positive relationship between the selected attraction factors and employees’ retention. The results also shown that the dominant factor that influenced the employees’ retention is job security. Thus, based on the findings, the company or HR practitioners may implement or improve the current factors to attract employees to retain in the company. Lastly, in order to gain future insight regarding the area of this study, the future researchers may use other attraction factors as the independent variables.